A Human-Centred Systems Theory of e-Agriculture Automation and Control Systems Adoption: An Empirical Study of the Social Effects of Digital Control and Automation Systems in Agricultural Communities. Issue 2 (2020) - Somers, Sinead O'Neill; Stapleton, Larry
Abstract: Climate change, biodiversity crises and other challenges impinge upon agricultural communities who must adapt to these pressures. However, in many countries agriculture lags behind other sectors in its uptake of digital automation and control systems on the farm. In spite of decades of research into technological innovation adoption factors we still do not have a good understanding as to why this sector is slower than others to adopt these new systems. This paper is based on a qualitative study of farmers in the south-east of Ireland which explored social effects in technology adoption. It draws out key themes associated with Irish farming as communities of knowledge networks, learning and innovation dynamics and cultural features, as well as tensions in relationships between farmers and institutions. From this analysis new theoretical "RooT" model is offered to reorient control and automation technology adoption theories and better support agricultural technology innovation.